Analisis Penambahan Zat Aditif pada Bio Solar terhadap Opasitas Kendaraan Bermesin Diesel - Hafid Ramadhan; Edi Elisa; I Gede Wiratmaja (Universitas Muhammadiyah Yogyakarta, 2022)
This study aims to find out the effect of mixing biodiesel and additives with various kinds of mixtures on the exhaust gas opacity of a 4-stroke diesel engine. In this study, two variations of the ratio of the mixture of bio-diesel and additives were used, namely bio-diesel with a mixture ratio of 2.5%: 97.5% and a mixture ratio of 1.25%: 98.75% for additives and bio-diesel. The method used in this study uses an experimental method where the data collection process is carried out through observation and documentation. Data collection was carried out 5 times a repetition using the Opacity Smoke Meter tool. From the results of the study, the variation of the mixture of 2.5%: 97.5% resulted in the lowest average exhaust gas opacity value, where there was a decrease in exhaust gas opacity by 20.8% compared to standard conditions (without the addition of additives). From the results of this study, it can be concluded that there is an impact of adding additives to biodiesel on exhaust gas opacity where the more additives added to biodiesel will further reduce exhaust gas opacity in vehicles with diesel engines.